STRATEGI EMPLOYEE BRANDING PULLMAN CIAWI VIMALA HILLS MELALUI KAMPANYE #DIVERSITYFORALL - Rinaldi, Aldi; Miftahul Jannah, Selfie (Penerbit Lafadz Jaya, 2024)
This research aims to investigate and analyze the Employee Branding strategy that Pullman Ciawi Vimala Hills implemented through the #DiversityforALL campaign. Employee Branding has become increasingly crucial in today's business world as it directly impacts a company's image and ability to attract high-quality prospective employees. In this context, the #DiversityforALL campaign was chosen as the research focus to explore how Pullman Ciawi Vimala Hills specifically leverages the concept of diversity as a core value in building and strengthening the brand image of their employees. The research methodology involves content analysis of the campaign, in-depth interviews with the HR management of Pullman Ciawi Vimala Hills, and surveys involving employee participation. The analysis results indicate that the Employee Branding strategy implemented through the #DiversityforALL campaign has created an inclusive and appealing corporate image for potential employees.